2023
DOI: 10.3390/ijms241512218
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Properties and Storage Stability of Chitosan–Starch Films Containing Micellar Nano/Microstructures with Turmeric and Hibiscus Extracts

Abstract: The dynamic development of the food industry and the growing interest of consumers in innovative solutions that increase the comfort and quality of life push the industry towards seeking pioneering solutions in the field of food packaging. Intelligent and active packaging, which affects the quality and durability of food products and allows one to determine their freshness, is still a modern concept. The aim of our study was to obtain two types of films based on chitosan and starch with micellar nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The possibilities of innovative modifications of natural polymer technology also allow the formation of nanometer-sized capsules. In the results of the scientific and research work of the team of Woszczak et al [67], it was reported that a polysaccharide-based biomaterial contain-ing micellar nano/microstructures with extracts of turmeric and hibiscus was obtained. The evaluation of the physicochemical parameters of the tested biocomposites by using methods such as Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-VIS) and SEM electron microscopy also in this case allowed us to document the efficiency of the method of synthesis of nanostructures, which also confirms the method of obtaining polysaccharide composites presented in this manuscript.…”
Section: Spectroscopic Analysis (Uv-vis and Atr-ftir)mentioning
confidence: 99%
“…The possibilities of innovative modifications of natural polymer technology also allow the formation of nanometer-sized capsules. In the results of the scientific and research work of the team of Woszczak et al [67], it was reported that a polysaccharide-based biomaterial contain-ing micellar nano/microstructures with extracts of turmeric and hibiscus was obtained. The evaluation of the physicochemical parameters of the tested biocomposites by using methods such as Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-VIS) and SEM electron microscopy also in this case allowed us to document the efficiency of the method of synthesis of nanostructures, which also confirms the method of obtaining polysaccharide composites presented in this manuscript.…”
Section: Spectroscopic Analysis (Uv-vis and Atr-ftir)mentioning
confidence: 99%